Implementasi Pembelajaran Nilai-Nilai Pancasila Sebagai Upaya Mitigasi Bencana Sosial Konflik Antar Etnis di NTB - Ramli Akhmad; Enok Maryani (Program Studi Pendidikan Geografi Universitas Hamzanwadi, 2020)
West Nusa Tenggara is a province inhabited by three main ethnic groups namely the Sasak, Samawa, and Mbojo tribes. Several problems triggered inter-ethnic conflict in West Nusa Tenggara, causing losses. This study aims to: 1) find out the root causes of inter-ethnic conflict in West Nusa Tenggara; 2) knowing how to respond to social disasters between ethnic conflicts; 3) formulating the concept of the values of Pancasila as a basis for learning disaster mitigation between ethnic conflicts. This research uses descriptive method with historiographic approach. Data are systematically collected and analyzed, especially those related to inter-ethnic conflict in NTB in the past. The results of the research show: 1) the background of inter-ethnic conflict in NTB is dominated by lack of communication, interests, emotional involvement, and weak self-control so that people are easily provoked; 2) social disasters between ethnic conflicts can be addressed or anticipated by learning in schools, especially using video media, so that it is known how inter-ethnic conflict occurs, what are the losses incurred, conclude and provide positive advice in overcoming ethnic conflict through group discussions; 3) the concept of Pancasila values that can be implemented in learning to minimize conflicts between ethnic groups, among others, believe in the unity of God, the creator of the environment and the universe and their contents, maintaining order, respecting the opinions of others, helping one another when conflicts occur and not damaging the environment and other public facilities.